2013
DOI: 10.1007/s13238-013-2113-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of NLRP3 inflammasome

Abstract: Infl ammasome is a large protein complex activated upon cellular stress or microbial infection, which triggers maturation of pro-inflammatory cytokines interleukin-1β and interleukin-18 through caspase-1 activation. Nod-like receptor family protein 3 (NLRP3) is the most characterized infl ammasome activated by various stimuli. However, the mechanism of its activation is unclear and its exact cellular localization is still unknown. We examined the potential co-localization of NLRP3 infl ammasome with mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…More interestingly, the observations of colocalization of NLRP3 inflammasome with LDs and suppression of IL-1β by LD inhibition imply that E-FABP-mediated LD formation provide a new platform for the effective activation of the inflammasome. Given the unknown cellular localization of inflammasomes and underappreciated functions of LDs (Farese, Jr. and Walther, 2009; Wang et al, 2013), our data suggest a new interaction between inflammasomes and LDs. Thus, E-FABP represents a new molecular link between overnutrition and metabolic inflammation through coupling fatty acid trafficking and inflammasome activation.…”
Section: Discussionmentioning
confidence: 84%
“…More interestingly, the observations of colocalization of NLRP3 inflammasome with LDs and suppression of IL-1β by LD inhibition imply that E-FABP-mediated LD formation provide a new platform for the effective activation of the inflammasome. Given the unknown cellular localization of inflammasomes and underappreciated functions of LDs (Farese, Jr. and Walther, 2009; Wang et al, 2013), our data suggest a new interaction between inflammasomes and LDs. Thus, E-FABP represents a new molecular link between overnutrition and metabolic inflammation through coupling fatty acid trafficking and inflammasome activation.…”
Section: Discussionmentioning
confidence: 84%
“…Following these early studies, co‐immunoprecipitation has confirmed NLRP3, ASC, and caspase‐1 oligomerization, but the molecular weight of these NLRP3 complexes remains to be directly assessed. Oligomerization of NLRP3 and ASC in HMW complexes has also been supported by immunofluorescent confocal microscopy studies showing co‐localization of NLRP3 and ASC in specks . However, biochemical determination of the predominant molecular weight of endogenous NLRP3 inflammasome complexes has yet to be determined and will be relevant to assess what constitutes an active inflammasome.…”
Section: Inflammasome Complex Assemblymentioning
confidence: 88%
“…In contrast to these studies supporting mitochondrial or MAM localization of NLRP3 inflammasomes, microscopy experiments by Wang et al . using a variety of organelle markers could not determine a specific localization of ASC specks, and because NLRP3 co‐localizes with the specks, the authors concluded that NLRP3 is cytosolic. However, association of NLRP3 with specific organelles was not independently examined, and as it is unclear whether the ASC speck represents an active NLRP3 inflammasome (discussed below), it is difficult to know whether or how these findings relate to NLRP3 localization.…”
Section: Mitochondrial Damage In Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…NLRP3 is expressed in the cytosol of various cell types, including granulocytes, monocytes, macrophages, dendritic cells, T and B cells, epithelial cells, osteoblasts, fibroblasts and melanoma cells . NLRP3 inflammasome is found distributed throughout the cytoplasm rather than within any specific organelles . Activation of NLRP3 leads to the homotypic protein–protein interaction between PYD of NLRP3 and the PYD of ASC.…”
Section: Expression and Activation Of The Nlrp3 Inflammasomementioning
confidence: 99%